PENGARUH CAPITAL ADEQUACY RATIO, NON PERFORMING RATIO, DAN LOAN TO DEPOSIT RATIO TERHADAP RETURN ON ASSETS PADA PT. BANK RAKYAT INDONESIA, TBK. - Nadi Hernadi Moorcy; Imam Arrywibowo (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2020)
Abstract, The Influence of Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), and Loan to Deposit Ratio Against Return on Assets (ROA) at PT. Bank Rakyat Indonesia, Tbk. The purpose of this study was to determine the effect of CAR, NPL, and LDR on ROA at PT. Bank Rakyat Indonesia, Tbk. The population used in this study are all Financial Statements of PT. Bank Rakyat Indonesia, Tbk. by using purposive sampling technique with criteria set by the author. The analysis used is multiple linear regression analysis method. Based on the test results simultaneously obtained that the variable CAR, NPL, and LDR simultaneously have a significant effect on ROA at PT. Bank Rakyat Indonesia, Tbk., While the CAR variable partially has a negative and significant and dominant influence on ROA at PT. Bank Rakyat Indonesia, Tbk., NPL has a negative and significant effect on ROA at PT. Bank Rakyat Indonesia, Tbk., And LDR have a negative and not significant effect on ROA at PT. Bank Rakyat Indonesia, Tbk.